1991
DOI: 10.1111/j.1365-2761.1991.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination experiments and studies of the humoral immune responses in cod, Gadus morhua L., to four strains of monoclonal‐defined Vibrio anguillarum

Abstract: Abstract. Vibrio anguillarum isolated from diseased cod, Gadus morhua L., were serotyped by use of a panel of monoclonal antibodies. Four serotypes could be distinguished, having different lipopolysaccharide determinants. These phenotypic differences were also reflected in the genetic map, as revealed by fingerprinting of bacterial DNA. Antisera were raised in cod after immunization with the V. anguillarum serotypes, and Western blot techniques demonstrated production of specific antibodies mainly to LPS‐anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…A T-cell independent antibody response, for example against polymeric structures like LPS, is low 84 compared to the antibody response to T-cell dependent antigens like proteins (Miller & Clem, 1984;Miller et al, 1985;Hoel et al, 1998). Vaccination of cod using formalin-killed Vibrio anguillarum or V. salmonicida produced good specific protection against these pathogens (Espelid et al, 1991;Schrøder et al, 1992). However, the specific humoral antibody response of cod immunised with these bacteria either by immersion or by i.p.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A T-cell independent antibody response, for example against polymeric structures like LPS, is low 84 compared to the antibody response to T-cell dependent antigens like proteins (Miller & Clem, 1984;Miller et al, 1985;Hoel et al, 1998). Vaccination of cod using formalin-killed Vibrio anguillarum or V. salmonicida produced good specific protection against these pathogens (Espelid et al, 1991;Schrøder et al, 1992). However, the specific humoral antibody response of cod immunised with these bacteria either by immersion or by i.p.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific humoral antibody response of cod immunised with these bacteria either by immersion or by i.p. injection was relatively poor and primarily directed against the bacterial lipopolysaccharide (LPS), a T-cell independent antigen (Espelid et al, 1991). A study by also indicated that cod did not produce antibodies against a protein antigen (oxazolone ovine albumin).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the functional role of the carbohydrate moiety of cod IgM are hampered by two factors: (i) the inability of cod to produce specific antibodies [34,45,46] and (ii) the limited growth and poor secretion of IgM by leucocytes in vitro (B. Magnadóttir, unpublished data). Both these factors limit the possibilities of studying, for example, the influence that the carbohydrate moiety might have on antigen binding, phagocytosis of pathogens/antigen or on complement activation, and the e#ects of various glycosylation enzymes/ enzyme inhibitors on the in vitro expression of carbohydrate on IgM.…”
Section: B Magnadóttir Et Almentioning
confidence: 99%